2016
DOI: 10.1080/03088839.2016.1185181
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and forecasting the demolition market in shipping

Abstract: We model the demolition market, an integral part of the international shipping industry. It is shown through the implementation of a Vector Autoregressive (VAR) model that international steel-scrap prices contribute decisively towards price discovery in the ship-demolition industry. Our finding is explained and attributed to the fact that the growth models of Southeast Asian countries, where the ship-demolition market is primarily located, rely on scrap metal imports. These are mainly obtained from the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 10 publications
0
37
0
1
Order By: Relevance
“…For instance, Yin, Luo and Fan (2016) use the volume of coal and iron ore from trade data as a demand proxy for regional freight rates in the Capesize drybulk market. In general, any research that deals with market fundamentals, such as the study by Kagkarakis, Merikas and Merika (2016) on demolition market dynamics, could benefit from AIS-derived tonne-mile demand data (see, Shi and Li, 2016, for a comprehensive review of the recent maritime transport literature).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Yin, Luo and Fan (2016) use the volume of coal and iron ore from trade data as a demand proxy for regional freight rates in the Capesize drybulk market. In general, any research that deals with market fundamentals, such as the study by Kagkarakis, Merikas and Merika (2016) on demolition market dynamics, could benefit from AIS-derived tonne-mile demand data (see, Shi and Li, 2016, for a comprehensive review of the recent maritime transport literature).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It appears from Figures 2 and 3 as well as the correlation matrix that the series of SCR exhibits similar behavior and is closely related with the DEM both in the tanker and dry bulk segments. In fact, the scrap prices contribute to the price discovery in the demolition market by leading the demolition prices (Kagkarakis et al 2016). Moreover, strong positive correlation is observed among the 4 supply variables (EAR, SEC, NEW and FL), particularly in the bulk carrier market, which is reasonable as an increase -for instance-in freight rates will trigger a raise in the vessels' secondhand and newbuilding values.…”
Section: Data Descriptionmentioning
confidence: 69%
“…The study concluded that despite its little contribution at a global level, the industry is vital to the steel production and growth in the domestic ship-demolition regions. Finally, in a recent econometric analysis Kagkarakis et al (2016) employed a vector autoregressive (VAR) model in order to examine the tanker demolition prices determination and conduct forecasts. The study modeled the demand side of the industry and indicated that the price of the steel-scrap which is exported overseas from the developed regions (US and EU) to Southeast Asia, lead the ship-demolition prices and contribute significantly to the price discovery in the sector.…”
Section: Source: Clarkson Research Services Limited Figure 1 Ship Dementioning
confidence: 99%
See 1 more Smart Citation
“…When both of the markets are in recession and there is no operating income, the owner has to either lay-up or scrap his/her vessel. Mikelis [13] and Kagkarakis et al [14] point out a positive correlation between the demolition prices and freight markets and claim that demolition price a vessel gets is not only determined by the shipping markets but mostly due to demand for the steel itself.…”
Section: Literature Reviewmentioning
confidence: 99%